1997
DOI: 10.1017/s0022215100138836
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblastoma of the nasal cavity arising from the perpendicular plate of the ethmoid bone

Abstract: The presence of a benign osteoblastoma in the ethmoid sinus is rare and only a few cases have been reported. This is a case of a benign osteoblastoma arising from the perpendicular plate of the ethmoid bone with extension to the nasal cavity. The diagnosis and management of this unusual lesion, as well as the histopathology and the imaging characteristics are reviewed. We also review the previously reported cases of benign osteoblastomas of different origin, with nasal cavity involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…[4] Osteoblastoma is osteoblastoma [7] and a nasal osteoblastoma occurring from the nasal bone periosteum have also been reported. [8] Similar to the age pattern observed by Mirra et al for osteoblastomas in the body, [6] six out of eight reported patients with nasoethmoid tumor have been in their first two decades [ Table 1], [9][10][11][12][13][14][15][16] although there is one report of this tumor occurring in a 69-year-old female. [14] The patient is usually brought to otolaryngologist with nasal obstruction, visible prominence over midface or proptosis.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…[4] Osteoblastoma is osteoblastoma [7] and a nasal osteoblastoma occurring from the nasal bone periosteum have also been reported. [8] Similar to the age pattern observed by Mirra et al for osteoblastomas in the body, [6] six out of eight reported patients with nasoethmoid tumor have been in their first two decades [ Table 1], [9][10][11][12][13][14][15][16] although there is one report of this tumor occurring in a 69-year-old female. [14] The patient is usually brought to otolaryngologist with nasal obstruction, visible prominence over midface or proptosis.…”
Section: Discussionsupporting
confidence: 67%
“…Recurrence free after 22 months Park et al [16] 13/M Exophthalmos CT, MRI Ethmoid sinus Transnasal endoscopy Well after 12 months a benign tumor of bone that is histologically very similar to osteoid osteoma; in the past, it was sometimes known as giant osteoid osteoma. In fact, authors considered size to be an important differentiating feature, and called any tumor exceeding 1.5 cm as osteoblastoma.…”
Section: Ct Mri Perpendicular Plate Of Ethmoid Excision By Bifrontalmentioning
confidence: 99%
“…Typically, an expansile lesion is seen, with remodelling of adjacent bone. It is usually well circumscribed, without bone destruction, and with large, discrete areas of bone density; alternatively, it may have a mixed osseous and fibrous appearance 13 …”
Section: Discussionmentioning
confidence: 99%
“…In the cases identified by our literature search, the most common approach to excision was via a lateral rhinotomy approach. This was employed in five of the reported cases 4 , 8 , 9 , 12 , 13 . This approach allows full exposure of the ethmoid sinus and the lateral wall of the nasal cavity.…”
mentioning
confidence: 99%
“…In the osteoid type, the tumor arises from the subcortical or medullary portion of the bone and usually affects the long bones and vertebrae. 9 Computed tomography usually demonstrates the origin and extent of the tumor, the presence of matrix mineralization, and the tumor delineation, which is depicted as a peripheral, thin bony shell. 6 The differential diagnosis of osteoblastomas includes not only other bony neoplasms, such as osteoma, osteoid osteoma, and osteogenic sarcoma, but also fibro-osseous lesions, such as ossifying fibroma, fibrous dysplasia, and the cementing-ossifying fibroma, or cementoma.…”
mentioning
confidence: 99%